Along the Italian route of End-of-life: the latest judicial evolution on assisted suicide - Andreani, Teresa (Bioethica, 2021)
In the last three decades, the dilemma of End-of-Life is one of the most disputed bio-juridical questions Italy is confronting with. By raising highly sensitive ethical, legal and political dilemmas, it has deeply divided the Italian society, the scientific community and the political arena. In the context of a raging controversy, the Italian Parliament has opted for silence. Thus, an evolutive, judicial route has marked the legal frame in response to numerous, concrete demands of recognition of the freedom of self-determination and value of dignity in the final phase of life. In this review article, an overview of the judicial evolution of the complex mosaic of end-of-life issues will be firstly offered through three cases, pillars on which the latest judicial evolution on assisted suicide lays its foundations. Secondly, the issue of assisted suicide will be singularly addressed through the examination of the Cappato case which has outlined the path for the historical ruling of the Italian Constitutional Court, no’242 of 2019 on the constitutional illegitimacy of the crime of assistance to suicide under article 580 of the Italian Criminal Code. Precisely, the Court has pointed out several, concurrent requirements in presence of which an active conduct directly connected with suicide is not criminally relevant: the autonomous and free formation of the individual will, the irreversible nature of the disease, the ongoing practice of a life-saving treatment, the intolerability of the physical or psychological sufferings and the mental capacity to self-determination. Among the numerous, emerging, interpretative questions, the latest Trentini case, in which the requirement of life-saving treatment has been interpreted as inclusive of pharmacological therapy and of every material, sanitary life-saving assistance, will be further evaluated. Conclusively, a cross section of the fragile interplay between the legislative power and the judiciary power will be depicted in reference to the main open interpretative questions related to the enforcement of the constitutional ruling and a portrait of the upcoming scenerios, as the existing legislative drafts and the prepositive referendum question, will be concisely examined.